O discurso de ódio racial e as redes sociais : análise reflexiva sob o espectro da Constituição Federal de 1988 - Litwinski, Tatiana Fortes (2018)
This research aims to analyze the discourse of racial hatred in social networks, having as panorama a democratic and plural society and the Federal Constitution of 1988. The intention is to contribute to unveiling a reality hidden by the misalignment of discourse and its implications in invisibility constitutional provisions and the establishment of an equitable and effective system. It is intended, firstly, to demonstrate that the externalization of offensive acts can not be considered conditio sine qua non for the characterization of hate speech. It seeks, therefore, to foster reflection on the discourse that reproduces and perpetuates racist practices. The study will address, in a second moment, the existence of a blind spot to the discourse of racist hatred that hinders the achievement of constitutional objectives. The scenario of racial invisibility collides with the constitutional foundation of the dignity of the human person. It will also deal with the foundations of the right to freedom of expression and its impact on the exposed scenario. Finally, the path of critical and reflexive analysis in the study of cases will be traced in order to investigate the practical applicability of the constitutional provisions, and especially the guidelines and the paradigm designed for the constitution of a true Democratic State of Right. The hypothesis of this work is that the Federal Constitution of Brazil expressly states an active protection and commitment with the human being and against any form of discrimination and prejudice and it has been verified that the "network society" aims at the maintenance of an ideological ignorance and a pact of silence regarding the discourses of racial hatred that obstructs its public thematization. The offensive and serious speech is shifted to the realm of vulgar, ironic and informal discourse. The research will use as a research technique the bibliographic review on the subject.